2019
DOI: 10.11604/pamj.2019.33.216.14898
|View full text |Cite
|
Sign up to set email alerts
|

Myoma praevia and pregnancy

Abstract: The association of myoma and pregnancy is becoming more frequent due to the increasing age of first pregnancy. It may affect the outcome of fertility, pregnancy, labor and peripartum course. A 37 years old patient was referred to our unit for discovering uterine leiomyoma at 37 weeks of pregnancy. Ultrasound screening showed a praevia isthmic leiomyoma measuring 16cm. A caesarean delivery was scheduled and a large interstitial isthmic uterine myoma measuring 25cm was found. Hysterectomy was corporeal. The post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…Preterm deliveries (10.5%) were recorded in the women we studied. This was similar in other studies on coexisting fibroid in pregnancy [11,12,13,14].Though uterine fibroids do not appear to increase the incidence of preterm premature rupture of membranes, other studies show the opposite [21,22]. There was no premature rupture of membranes in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Preterm deliveries (10.5%) were recorded in the women we studied. This was similar in other studies on coexisting fibroid in pregnancy [11,12,13,14].Though uterine fibroids do not appear to increase the incidence of preterm premature rupture of membranes, other studies show the opposite [21,22]. There was no premature rupture of membranes in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Others are increased caesarean delivery, prolonged or obstructed labour, uterine rupture, ante partum, intra partum and post partum haemorrhage as well as uterine inversion and puerperal sepsis [9,11]. The babies are prone to early fetal loss, prematurity, fetal distress, newborn special care unit admission, perinatal morbidity and mortality [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The association of myoma and pregnancy is becoming more frequent due to the advanced maternal age. 16 In our study, 14.5% of 172 pregnant women had uterine fibroids with a diameter < 5 cm.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, most studies indicate the possibility of progressive growth of leiomyomas during pregnancy, which may be due to changes in hormone levels. The authors of scientific works note that the average increase in the volume of the fibroid is 12.6 %, while the maximum indicators can reach 25 % of the initial values [2]. In this regard, Vergani et al (2007) in their retrospective cohort study found that the risk of cesarean section before labor could increase by 26 % for every 1 cm increase in leiomyoma diameter [7].…”
Section: Introductionmentioning
confidence: 99%
“…Norwitz (2014), the prevalence of uterine leiomyoma among pregnant women reaches up to 10.7 %, depending on the trimester of pregnancy, while in women aged 35 to 42 years, the incidence increases by 20 % (from 19 to 25 years oldup to 12 %, from 35 to 42 years oldup to 32 %). This is due to an increase in the number of late pregnancies, which may be complicated by the presence of fibroids or previous myomectomy [1][2][3]. In addition, most studies indicate the possibility of progressive growth of leiomyomas during pregnancy, which may be due to changes in hormone levels.…”
Section: Introductionmentioning
confidence: 99%